A Rare Case of Severe Metabolic Alkalosis with Unusual Hyperproteinemia Treated with Continuous Renal Replacement Therapy and Regional Citrate Anticoagulation - Matoušek, Vojtěch; Herold, Ivan; Holanová, Lenka; Balík, Martin (Case reports in nephrology and dialysis, 2018)
A 23-year-old woman was referred to the tertiary centre with acute kidney injury and severe metabolic alkalosis following an accidental ethylene glycol poisoning. The patient had been treated with continuous haemodiafiltration and regional citrate anticoagulation, and a tracheostomy was performed due to pneumonia. Besides severe metabolic alkalosis and hypernatremia, the laboratory tests revealed total protein of 108 g/L on admission to the tertiary centre. The haemodiafiltration with regional citrate anticoagulation continued with parallel correction of the alkalosis and normalisation of the total plasma protein. The tracheostomy was decannulated and the patient was discharged to the district hospital. The case demonstrates the usefulness of regional citrate anticoagulation even in severe metabolic alkalosis which was likely related to the method setting prior to admission and to an overcompensation of the initial severe metabolic acidosis. The unusual hyperproteinaemia might be interpreted with the aid of the Stewart-Fencl model of the acid-base regulation.
Keywords: Hyperproteinaemia; Stewart-Fencl acid base concept; Metabolic alkalosis; Regional citrate anticoagulation; Continuous renal replacement therapy; Citrate accumulation